Influence of Seed Vigour on Seed Quality and Yield in Okra (Abelmoschus esculentus L.) - M. ARUN KUMAR; K. KESHAVULU; N. MANOHAR REDDY; R. ANKAIAH; M. GANESH (Seed Research, 2026)
An experiment was conducted to determine the influence of seed vigour on initial seed quality and yield of okra hybrid during Rabi 2002-03. The Sun 008 hybrid with four vigour levels after accelerated ageing constituted the treatments. The germination, seedling vigour, seedling dry weight and field emergence decreased with increased period of accelerated aging. Thus ultimately affected the plant height, dry matter production per plant, leaf area per plant, number of fruits per plant, number of seeds per fruit and seed yield with the declining trend of germination levels from 94% (control) to 54% germination.